2008
DOI: 10.1002/chem.200801600
|View full text |Cite
|
Sign up to set email alerts
|

A General and Environmentally Benign Catalytic Reduction of Nitriles to Primary Amines

Abstract: Dedicated to Professor Günther Oehme on the occasion of his 70th birthdayA vast number of amines are produced by both the bulk and fine chemical industries, and a plethora of naturally occurring nitrogen compounds, such as alkaloids, amino acids, and nucleotides, play a pivotal role in biological processes. [1] During recent decades, several novel catalytic methods have been established for the synthesis of amines, such as palladium-catalyzed amination of aryl halides, [2] hydroaminations [3] and hydroaminomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Moreover, it is well known that the hydrogenation of PhCN to benzylamine is catalysed by molecular complexes [22][23][24]. In the case of metal surfaces [20,21,25] the activated amine -benzylamine -is rapidly transformed into the benzylidene benzylamine via aminolysis and coupling although we were unable to detect neither benzylamine nor benzylimine by ESI-MS and NMR experiments.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, it is well known that the hydrogenation of PhCN to benzylamine is catalysed by molecular complexes [22][23][24]. In the case of metal surfaces [20,21,25] the activated amine -benzylamine -is rapidly transformed into the benzylidene benzylamine via aminolysis and coupling although we were unable to detect neither benzylamine nor benzylimine by ESI-MS and NMR experiments.…”
Section: Resultsmentioning
confidence: 56%
“…In the case of metal surfaces [20,21,25] the activated amine -benzylamine -is rapidly transformed into the benzylidene benzylamine via aminolysis and coupling although we were unable to detect neither benzylamine nor benzylimine by ESI-MS and NMR experiments. As already pointed out benzylamine undergoes exclusively aminolysis with solid catalysts, in contrast molecular catalysts give benzylamine as main product [22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Even better catalytic performance and functional group tolerance was obtained with an easily accessible in situ catalyst composed of [Ru(cod)methylallyl 2 ] and DPPF [53]. Here, under optimized conditions, a superior catalyst activity with a turnover frequency (TOF) of up to 5783 h -1 has been achieved in the hydrogenation of the benchmark substrate.…”
Section: Resultsmentioning
confidence: 82%
“…[15,17] Recently, we demonstrated that an in situ catalyst system composed of [RuA C H T U N G T R E N N U N G (cod)(methylallyl 2 )] (cod = 1,5-cyclooctadiene) and 1,1'-bis(diphenylphosphino)ferrocene (dppf) allows for excellent chemoselectivities (> 99 %) towards primary amines and high turnover frequencies up to 5783 h À1 . [18] Herein, we report our ongoing studies of the catalytic reduction of nitriles. For the first time, it is shown that straightforward ruthenium complexes modified by cheap and available triphenylphosphine allow for the efficient and general reduction of various kinds of aryl and alkyl nitriles.…”
Section: Introductionmentioning
confidence: 99%